2010
DOI: 10.1366/000370210792434288
|View full text |Cite
|
Sign up to set email alerts
|

The Unique Molecular Behavior of Water at the Chloroform—Water Interface

Abstract: The molecular bonding and orientation of water at the chloroform-water interface has been examined in this study using vibrational sum-frequency spectroscopy (VSFS). The results provide a key puzzle piece towards our understanding of the systematic changes in the interfacial bonding and orientation of water that occur with variations in the polarity of the organic phase, especially when compared with previous studies of different liquid-liquid interfacial systems. In these VSFS studies the OH spectral response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 77 publications
3
13
0
Order By: Relevance
“…For these water molecules, one OH bond is oriented toward the FDS surface (free OH), with which it weakly interacts, and the companion OH protrudes into the aqueous phase and is red shifted from the free OH due to its bonding interactions with other interfacial water molecules. Such sharp peaks were previously reported at the air-water 46,60 , organic liquid-water, 61,64 and solid-water interfaces. 10,65,66 The frequency of this peak is a measure of the strength of the interaction between water and the hydrophobic phase.…”
Section: Resultssupporting
confidence: 83%
“…For these water molecules, one OH bond is oriented toward the FDS surface (free OH), with which it weakly interacts, and the companion OH protrudes into the aqueous phase and is red shifted from the free OH due to its bonding interactions with other interfacial water molecules. Such sharp peaks were previously reported at the air-water 46,60 , organic liquid-water, 61,64 and solid-water interfaces. 10,65,66 The frequency of this peak is a measure of the strength of the interaction between water and the hydrophobic phase.…”
Section: Resultssupporting
confidence: 83%
“…Isotope scrambling data suggested that CO 2 reacted with adsorbed water to yield adsorbed carbonate and protonated surface groups, M-OH 2 + , via a proposed carbonic acid intermediate, H 2 CO 3 , 88 a rather elusive chemical species albeit an important one (M -metal atoms on the surface). The proposed reaction mechanism is shown in eqn ( 18) through (21). Quantum chemical calculations supported the formation of solvated carbonate ions on the surface.…”
Section: Carbon Dioxidementioning
confidence: 81%
“…These differences further control the thermodynamics of solvation, stability, permeability, reactivity and other molecular properties of water at the interface. 14 Recent studies by Shamay et al and others 20,21 have highlighted the influence of hydrogen bonding on the orientation of surface water molecules in the presence of adsorbed gases (e.g. CO 2 and SO 2 ) and organic molecules (e.g.…”
Section: Water -Brief Comments On Water In Different Phases and Clust...mentioning
confidence: 99%
See 1 more Smart Citation
“…We know, for example, that weak bonding interactions between interfacial water and various hydrophobic oils is a general trait for these oil-water systems, resulting in significant molecular orientational ordering and structuring of both phases near the interfacial region (13)(14)(15). The existence of an interfacial electric field created by this structuring has been shown to facilitate the adsorption of simple electrolyte ions at the interface (15), surfactant adsorption, and also the penetration of oriented water into the organic phase (16).…”
mentioning
confidence: 99%